2016
DOI: 10.1016/j.bandl.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the time course of lexical access in orthographic production: An event-related potential study of word frequency effects in written picture naming

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms AbstractPrevious studies of spoken picture naming using event-related potentials (ERPs) have shown that speakers initiate lexical access within 200 ms after stimulus onset. In the present study, we investigated the time course of lexical access in written, rather than spoken, word pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
31
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 61 publications
9
31
2
Order By: Relevance
“…People spend less time preparing to write and actually writing a more frequent character, and they are also more accurate at writing it. These frequency effects are consistent with previous findings in handwriting (e.g., Kandel & Perret, 2015;Qu et al, 2016;, and indeed also in spoken word/character production (e.g., Balota & Ferraro, 1993;Chang et al, 2016;Jescheniak & Levelt, 1994;Lee et al, 2005). A similar advantage in writing latency, writing duration, and accuracy is also observed when a character is embedded in a more familiar word.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…People spend less time preparing to write and actually writing a more frequent character, and they are also more accurate at writing it. These frequency effects are consistent with previous findings in handwriting (e.g., Kandel & Perret, 2015;Qu et al, 2016;, and indeed also in spoken word/character production (e.g., Balota & Ferraro, 1993;Chang et al, 2016;Jescheniak & Levelt, 1994;Lee et al, 2005). A similar advantage in writing latency, writing duration, and accuracy is also observed when a character is embedded in a more familiar word.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent some previous studies. For instance, Qu and colleagues (Qu et al, 2011;Qu et al, 2016) showed that a masked prime that is phonologically related to a subsequent target character can facilitate handwriting of the target character; Kandel and Perret (2015) showed longer handwriting latencies (for accessing orthographic codes) for words that are irregular rather than regular in spelling. These findings suggest that people can make use of phonological cues to facilitate access to the target orthographic representations.…”
Section: The Role Of Phonology In Handwritingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to measure writing‐specific sex differences appropriately, other handwriting‐related variables including reading, cognitive, and basic visual‐motor skills were matched between males and females. Word frequency is a vital language factor that influences orthographic access and motor execution during handwriting (Kandel & Perret, ; Qu, Zhang, & Damian, ; S. Roux, Mckeeff, Grosjacques, Afonso, & Kandel, ; Zhang & Cheng, ). Previous fMRI studies have demonstrated that word frequency modulates brain activity related to handwriting in superior/middle frontal gyrus, inferior parietal lobule and fusiform gyrus (Rapp & Dufor, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A new sequence was generated for each participant and each block. Note that a design in which each target is presented and named multiple times is quite common in spoken word production and usually considered to be unproblematic (i.e., Zhu et al, 2015;Qu et al, 2016;Zhang and Damian, 2019). Nevertheless, in the latency analysis reported below, we included "repetition" as an addition factor to check for potential effects of multiple target presentation.…”
Section: Stimuli and Designmentioning
confidence: 99%